Serum Vitamin D Level and Body Mass Index in Children with Vernal Keratoconjunctivitis - Gonul Karatas Durusoy; Yalcin Karakucuk; Beril Tulu Aygun; Banu Solmaz (Beyoglu Eye Journal, 2020)
INTRODUCTION[|]The purpose of this study was to evaluate the body mass index (BMI) value and serum 25-hydroxyvitamin D [25(OH)D3] level in children with vernal keratoconjunctivitis (VKC).[¤]METHODS[|]A total of 40 healthy, non-atopic children (control group) and 46 children with VKC (study group) were included in the study. The serum vitamin D [25(OH)D3] levels and BMI values were measured and compared between the 2 groups.[¤]RESULTS[|]The mean vitamin D level measured in the healthy children (mean: 19.01+-5.66 ng/mL, range: 9–33.09 ng/mL) was significantly different from the mean vitamin D level in the VKC-affected children (mean: 14.06+-5.02 ng/mL, range 4.37–31 ng/mL) (p<0.001). The mean BMI in the VKC group (17.1+-2.5 kg/m2) was significantly higher than the mean BMI of the healthy children (mean: 16.5+-2.3 kg/m2; p=0.046). A negative correlation (Spearman's rho=-0.275; p=0.01) was observed between the vitamin D level and the BMI value.[¤]DISCUSSION AND CONCLUSION[|]The results indicated that children with VKC had a lower serum vitamin D level and a higher BMI value compared with healthy, age- and sex-matched children.[¤]